PENEGAKAN HUKUM TERHADAP PELAKU PELECEHAN SEKSUAL DI KEPOLISIAN KOTA BATAM (STUDI DI POLSEK BATAM KOTA) - Mustholih, Khairil; Jamba, Padrisan (SCIENTIA JOURNAL, 2019)
This stduy aiims to find out how law enfoili rcement against perpetrili ators of sexual harassment in Batam City Pili olice and to find out what are the obstacles of Batam Sector Police in law enfili orcemeili nt against sexual hili arassers. This study uses a qualitative approach. The researchl er used priimary legal materials, namely mateili rials obtained from direct interviews with Memili bers of the Batam Sector Police Tigor Dabariba, SH, the women's service unit and Bripda Helmiatun children and secondary and tertiary legal materiials obtaiined from the literature. The results of thili is study iindiili cate that law enforili cement against perpetrators of sexual haraili ssment in the jurisdili iction of the Batam Ciity Sector police can be punished basili ed on the Kili UHP for a maximum of 15 (fifteen) years in priisili on and can be added with adili dil tional demili ands and if the victiilil ms are children. The Batam Sectol r Pili olice obstl acle in law enili forcement against perpetraili tors of sexual harassment is difficult to find the whereabouts of perpetrators of criiminal acts of sexual harassment / molestation who have fled and becili ome fugiitives; limiitted time in completting cases; llack of inforili maition abili out the perpetrator; the difficulty of asking for information from witnesses as victims of trauma; high cost of post mortem; lack of adequate facillities and infraistili ructure for the investili igation and disclosuili re of criminal acts of sexual viollence against chilldren in the Batam Ciity Police Sector PPA Unit.